Evaluation of Culture Representation in Vision English Textbook Series for Iranian Secondary Public Education - Mojtaba Gheitasi; Mohammad Aliakbari; nourodin Yousofi (Journal of English Language Teaching and Learning, 2020)
This study evaluated the cultural content of Vision textbook series that are currently in use in Iranian public secondary school system. The aim was to find the most frequent cultural references as well as the most-frequently-represented cultural senses. For this purpose, frequency counts were used to collect the data and the culture categorization framework (Adaskou et. al., 1990) and cultural reference framework (Cortazzi & Jin, 1999), modified by Tajeddin and Teimournezhad (2014), were used to analyze the data. Results of the frequency counts indicated that the Vision ELT textbooks contained the most cultural content associated with Persian as the source culture. Similarly, the focus was primarily on the esthetic sense of culture, followed respectively by semantic, sociological and sociolinguistic (pragmatic) senses. The study ends up with implications for EFL stake-holders in Iranian context as well as the ELT enterprise in general.